Attitudes and perceived barriers to mental healthcare in the People's Liberation Army Navy: study from a navy base. Issue 5 (18th May 2020) - Gu, Ren-Ping; Liu, X R; Ye, X F
Abstract : Introduction: The People's Liberation Army (PLA, China) Navy is increasingly conducting military operations other than war overseas. Factors such as confrontations with pirates, special environments and long sailing times have resulted in mental health problems. However, the navy's actual utilisation of mental health services is low. This study examined members' rate of willingness to seek help and the factors that act as barriers to willingness to seek mental health services in the PLA Navy. Methods: This cross-sectional study was conducted at the Zhoushan Base, operated by the East Sea Fleet, between March 2019 and April 2019. We distributed a 12-item questionnaire to examine participants' attitudes and perceived barriers to mental healthcare. We recruited 676 navy personnel. Participants' willingness to seek help if they had mental health problems was also assessed. Results: The response rate was 99%. A total of 88.44% of the sample reported being willing to seek help. Univariate analysis suggested that those not willing to seek help were more likely to agree with the items, ' Mental healthcare does not work ' and ' My unit leadership might treat me differently ' and all organisational barriers, and they were more likely to have concerns about ' embarrassment ' and ' being weak ' than those willing to seek help. After controlling for demographic characteristics, binary logistic regression analyses confirmed that a lack of knowledge regarding the location of mental health clinics and being perceived as weak were the main factors preventing participants' willingness from seeking help. Conclusions: Extensive efforts to decrease organisational barriers and stigma towards mental healthcare should be a priority for researchers and policymakers to improve the usage of mental health services. Psychoeducation aimed at de-stigmatising mental health problems should be delivered and the accessibility and availability of mental health services should be increased.